Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1471-2458-13-967
|View full text |Cite
|
Sign up to set email alerts
|

Child-oriented marketing techniques in snack food packages in Guatemala

Abstract: BackgroundChildhood overweight in Guatemala is now becoming a public health concern. Child-oriented marketing contributes to increase children’s food preference, purchase and consumption. This study sought to assess the availability of child-oriented snack foods sold in school kiosks and convenience stores near public schools in Guatemala, to identify the marketing techniques used in child-oriented snack food packages and to classify the snacks as “healthy” or “less-healthy”.MethodsWe purchased all child-orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 21 publications
6
66
0
2
Order By: Relevance
“…This price parity resulted in a situation whereby processed foods remain highly available and affordable, even while fresher, more nutritious foods were more expensive or unavailable. These findings are consistent with other literature showing the rapid incursion of processed foods marketing in urban, non-indigenous Guatemalan populations [17,18]. They are also consistent with the global scholarly literature, which has repeatedly demonstrated that the commoditization of diets decreases dietary diversity in both rural and urban settings [35,36].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This price parity resulted in a situation whereby processed foods remain highly available and affordable, even while fresher, more nutritious foods were more expensive or unavailable. These findings are consistent with other literature showing the rapid incursion of processed foods marketing in urban, non-indigenous Guatemalan populations [17,18]. They are also consistent with the global scholarly literature, which has repeatedly demonstrated that the commoditization of diets decreases dietary diversity in both rural and urban settings [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the implementation of small-plot household gardens could improve dietary diversity and serve as bridge to more large-scale transitions in cropping practices [32,33]. Finally, exploration of strategies to improve the availability of fresh foods in local corner stores with packaging and pricing that makes them competitive to processed foods is essential to improving dietary quality [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the outset, it is important to note that the codes for child marketing and nutrition were developed as cumulative measures of both types of marketing approaches, as the presence of more of these cues indicates a more concerted effort to highlight these particular attributes. Development for the childtargeted marketing code was based on previous research (20,(30)(31)(32)(33) . Each package was assessed for the presence of each of the following eight characteristics: (i) child-friendly imagery (e.g.…”
Section: Coding Proceduresmentioning
confidence: 99%
“…Package design plays a major role in attracting attention and influencing purchase intent, and provides food companies the last chance to persuade consumers to buy the product at the point of sale 23 . Foods targeted at children are usually marketed using unconventional flavor and colors, cartoon characters, photos of celebrities, household names, merchandising tie-ins, and direct references to fun and play on the packages 22,24,25,26 . These marketing strategies have been reported to encourage children to think that products are tastier, healthier, funnier, and more appropriate for them, increasing their liking and willingness to consume 27,28 .…”
Section: Introductionmentioning
confidence: 99%